COMPARATIVE ANALYSIS OF GREEN ICT PRACTICES AMONG PALESTINIAN AND MALAYSIAN IN SME FOOD ENTERPRISES DURING COVID-19 PANDEMIC - Malik Mustafa, Abdallah Abbas (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
Covid-19 requires the demand to spread awareness among people about the adverse environmental impact of operations done in industries in order to sustain the environment. For that purpose, green information & technology devise the standard in order to incorporate strategies practically to gain a wide range of economic benefits special under critical circumstances of pandemic. Besides, Green ICT plays a significant role in promoting Sustainability in industrial context. Sustainability has become an essential factor for companies and industries nowadays, especially food industry. This study explores a comparative analysis between Palestine and Malaysian food industries in the context of Green ICT during this pandemic. This study comprises of; firstly, analyze the food practices in food industry. Secondly, to investigate the basic factors that affect Sustainability in align to literature. The results of the research showed that environmental, economical, technological and social responsibility are few of those factors that affect the practices. Data was collected with the help of a questionnaire survey, 200 SME managers from the food industry in which 100 from Palestinian food firms and 100 from Malaysian food firms. 60% was the response rate for the survey. SPSS was used to analyze the Validity and Reliability of the data collected earlier. T-sample test was run to examine the effect of different factors. The study concludes that there is a significant influence of suitability operations in the food industry while comparing Palestine and Malaysia. Thus, it revealed that Malaysian food chain firms were considered as more competent in incorporating Green ICT in terms of Technical and environmental factors as compared to Palestine industries during this pandemic, COVID-19. Furthermore, adopting of ICT helped in enhance the efficiency of environmental supply chain and boost competitive advantage.